2002
DOI: 10.1074/jbc.m112406200
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-dependent Metabolism of Platelet-activating Factor in Murine Macrophages

Abstract: Degradation of platelet-activating factor (PAF) was examined by incubating PAF with macrophages from PAF receptor-deficient mice. The degradation rate was halved as compared with wild-type mice. The reduction of the rate was comparable with the presence of a PAF antagonist WEB 2086 in wild-type cells. PAF was internalized rapidly (t1 ⁄2 Ϸ 1 min) into wild-type macrophages. The PAF internalization was inhibited by the treatment of 0.45 M sucrose but was not affected by phorbol 12-myristate 13-acetate, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Fluorescent intensity was quantified by comparison to resolved fluorescent standards. Cytosolic and extracellular lipids were fractionated from B-PAF-treated cultures with an acidified methanol wash separating phospholipids bound to proteins on plasma membrane from internalized lipids (36). We found that 1 M B-PAF was stable in cell-free, serum-free treatment media at 37°C for at least 60 min; no degradation to B-lyso-PAF was observed in the absence of cells (Fig.…”
Section: Cytosolic Paf-ah Enzymes Limit the Duration Of Paf-inducedmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescent intensity was quantified by comparison to resolved fluorescent standards. Cytosolic and extracellular lipids were fractionated from B-PAF-treated cultures with an acidified methanol wash separating phospholipids bound to proteins on plasma membrane from internalized lipids (36). We found that 1 M B-PAF was stable in cell-free, serum-free treatment media at 37°C for at least 60 min; no degradation to B-lyso-PAF was observed in the absence of cells (Fig.…”
Section: Cytosolic Paf-ah Enzymes Limit the Duration Of Paf-inducedmentioning
confidence: 99%
“…Passive PAF internalization is regulated by transbilayer movement (flipping) across the plasma membrane occurring as a result of physicochemical changes in membrane properties accompanying cellular activation (15). It has been suggested that PAF internalization in the absence of PAFR is not rapid enough to elicit acute biological activity in hematopoietic cells (36,49). In this study, we present evidence that PAFR-independent PAF internalization by nonhematopoietic cells is indeed sufficient to trigger apoptotic cell loss.…”
Section: Cytosolic Paf-ahs Can Be Targeted Pharmacologically To Promomentioning
confidence: 99%
See 1 more Smart Citation
“…Murine peritoneal macrophages were previously shown to metabolize PAF when cells were incubated with [acetyl-3 H]PAF, and the aqueous degradation products of PAF gradually accumulated in the culture medium in a time-dependent manner (47). Using this system we investigated the effect of deficiency of PAF-AH (II) on PAF degradation by murine peritoneal macrophages.…”
Section: Paf-ah Activity In Pafah2mentioning
confidence: 99%
“…PAF Degradation Assay-PAF degradation by cultured peritoneal macrophages was measured as described (47). Peritoneal exudate macrophages were obtained by washing the peritoneal cavity with 5 ml of ice-cold phosphate-buffered saline 3 days after intraperitoneal injection of 2 ml of sterile 4% thioglycollate.…”
Section: Generation Of Pafah2mentioning
confidence: 99%